Selecting and defining transversal competences for higher education training design - Khaled Gijón, Meriem; Ávalos Ruiz, Inmaculada; de Rueda Villén, Belén; García de Quesada, Mercedes (Frontiers in Education, 2025)
Transversal competences, such as flexibility, collaboration or critical thinking, are proving to be key not only in academic performance but also in professional and personal performance. In response to a growing demand for research and training in these competences, this study originates from a teaching innovation project at the University of Granada (Spain) with the aim of designing the base structure of a psycho-educational intervention aimed at undergraduate students at the Spanish public university. For this purpose, the European framework for Personal, Social and Learning to Learn Key Competence, LifeComp, is used as the base line. This work proposes a coherent, pedagogically sound, general competence-based programme that blends with the official, more-specific competence-based curriculum, to deepen learning and proactively respond to the complex challenges our society is currently facing. In order to do so, different levels of proficiency for each of the nine LifeComp competences are suggested, as well as an outline for the design of the training action. This work has served as the basis for the creation of a psycho-educational training programme whose parallel study has been registered on www.clinicaltrials.gov under NCT05598944 and NCT NCT05775978 registries. The resulting programme is currently being taught to all undergraduate students at the University of Granada (Spain).